Preventing pathological scar formation: treatment of surgical scars with mixed technology: fractional CO2 laser plus Er:Glass laser - Flagiello, Francesca; Antoniadou, Kristallia; Centofanti, Domenico; Bartoletti, Emanuele; Cavalieri, Loredana (Aesthetic Medicine, 2025)
Background: Scar treatment is a very challenging field. One of the major challenges in managing scars is their variability, which depends on the patient's etiology, severity, distribution, skin type, comorbidities, genetics, age, changes over time, and patient compliance, to name just a few. Despite best efforts and research over the decades, the quality of analytical studies on scars remains unsatisfactory compared to other fields of clinical and scientific activity. However, doctors and scientists continue to work to implement clinical and scientific strategies aimed at making treatments more effective. Objective: to study the new Mixed technology (MT) laser technology to prevent the formation of pathological scars during the wound healing process. Method: To this end we used a laser YouLaser mixed technology (MT) laser whose characteristic consists in the combination of two different wavelengths: fractional CO2 laser (10600 nm - ablative) and Er:Glass laser (1540 nm - non-ablative). 15 patients were enrolled and 20 surgical scars were selected. The protocol was completed on 7 patients for a total of 13 scars, of which 6 women and 1 man, with ages between 20 and 60 years and phototype according to Fritzpatrick between I and III. The selected scars were the results of surgery performed less than 6 months ago. Results: The severity and characteristics of scars were assessed via photographic images and using the POSAS (The Patient and Observer Scar Assessment Scale) questionnaire, a standardized and internationally recognized tool for scar assessment. The collected data were analyzed and interpreted with the help of a specific Likert scale, allowing a statistical evaluation of the progress of the severity and characteristics of the scars. All the characteristics analyzed showed a significant improvement, with scores that went from an average value of 6 to significantly lower values, between 2 and 4. The results showed significant improvements in terms of texture, color and thickness of the treated scars. Conclusions: According to the results of this study, early intervention on recent scars is effective because it guarantees preventive activity on the lesions, blocking the pathological evolution of the scars themselves. This is confirmed by the fact that one year after the surgery none of them had a pathological course in the hypertrophic or keloid sense.